Implementation of routine foot check in patients with diabetes on hemodialysis: associations with outcomes. Issue 1 (3rd March 2016) - Marn Pernat, Andreja; Peršič, Vanja; Usvyat, Len; Saunders, Lynn; Rogus, John; Maddux, Franklin W; Lacson, Eduardo; Kotanko, Peter
Abstract : Objective: Patients with diabetes are at increased risk of foot ulcers, which may result in limb amputations. While regular foot care prevents ulcerations and amputation in those patients with diabetes not on dialysis, evidence is limited in diabetic hemodialysis patients. We investigated the association between the implementation of a routine foot check program in diabetic incident hemodialysis patients, and major lower limb amputations. Methods: In 1/2008, monthly intradialytic foot checks were implemented as part of standard clinic care in all Fresenius Medical Care North America hemodialysis facilities. Patients with diabetes who initiated hemodialysis between 1/2004 and 12/2007 constituted the preimplementation cohort, and patients starting hemodialysis between 1/2008 and 12/2011 comprised the postimplementation cohort. In addition, we conducted a sensitivity analysis where we excluded patients from the clinics with <10 patients in the postimplementation period and where percent difference in patient with diabetes number between postimplementation and preimplementation period was <20%. We compared lower limb amputation rates employing Poisson regression models with offset of exposure time in these two cohorts. Results: We studied 35 513 patients in the preimplementation and 25 779 patients in the postimplementation cohort. In the postimplementation cohort, amputation rate decreased by 17% (p=0.0034). The major lower limb amputation rate was 1.30 per 100 patient years in preimplementation and 1.07 in postimplementation cohort. These beneficial results were corroborated in the multivariate analysis (p=0.0175) and were even more pronounced in the sensitivity analysis (p=0.0083). Conclusion: Monthly foot checks are associated with reduction of major lower limb amputations in diabetic incident hemodialysis patients.